When did "teaching" become a taboo word for clinician educators?. (1st February 2020) - Pylman, Stacey; Ward, Amy
Abstract: In our recent work with clinician educators leading UME small groups, we noticed a phenomenon – many clinician educators are saying they don't teach, they just facilitate. Medical schools have moved to a new model of curriculum that integrates basic, clinical, and social science concepts. As curriculum shifts, so too must the definition and role of a teacher in medical education. The purpose of this article is to explore the work of current clinician educators and to encourage clinician educators to embrace their teaching role and seek educator development opportunities. In this article, we explore the history of how and why the word "teaching" became taboo for clinician educators. Then we explain the current state of the complex work of teaching for today's clinician educators and its implications for educator development.